Case study: Muscle atrophy and hypertrophy in a Premier League soccer player during rehabilitation from ACL injury - Burgess, D. J.; Morton, J. P.; Milsom, J.; Barreira, P.; Iqbal, Z. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
The onset of injury and subsequent period of immobilization and disuse present major challenges to maintenance of skeletal muscle mass and function. Although the characteristics of immobilization-induced muscle atrophy are well documented in laboratory studies, comparable data from elite athletes in free-living conditions are not readily available. We present a 6-month case-study account from a professional soccer player of the English Premier League characterizing rates of muscle atrophy and hypertrophy (as assessed by DXA) during immobilization and rehabilitation after ACL injury. During 8 weeks of inactivity and immobilization, where the athlete adhered to a low carbohydrate-high protein diet, total body mass decreased by 5 kg attributable to 5.8 kg loss and 0.8 kg gain in lean and fat mass, respectively. Changes in whole-body lean mass was attributable to comparable relative decreases in the trunk (12%, 3.8 kg) and immobilized limb (13%, 1.4 kg) whereas the nonimmobilized limb exhibited smaller declines (7%, 0.8 kg). In Weeks 8 to 24, the athlete adhered to a moderate carbohydrate-high protein diet combined with structured resistance and field based training for both the lower and upper-body that resulted in whole-body muscle hypertrophy (varying from 0.5 to 1 kg per week). Regional hypertrophy was particularly pronounced in the trunk and nonimmobilized limb during weeks 8 to 12 (2.6 kg) and 13 to 16 (1.3 kg), respectively, whereas the previously immobilized limb exhibited slower but progressive increases in lean mass from Week 12 to 24 (1.2 kg). The athlete presented after the totality of the injured period with an improved anthropometrical and physical profile.